Data_Sheet_1_Marine CO2 Patterns in the Northern Salish Sea.docx - Wiley Evans; Katie Pocock; Alex Hare; Carrie Weekes; Burke Hales; Jennifer Jackson; Helen Gurney-Smith; Jeremy T. Mathis; Simone R. Alin; Richard A. Feely (2019)
Marine carbon dioxide (CO 2 ) system data has been collected from December 2014 to June 2018 in the Northern Salish Sea (NSS; British Columbia, Canada) and consisted of continuous measurements at two sites as well as spatially- and seasonally distributed discrete seawater samples. The array of CO 2 observing activities included high-resolution CO 2 partial pressure (pCO 2 ) and pH T (total scale) measurements made at the Hakai Institute’s Quadra Island Field Station (QIFS) and from an Environment Canada weather buoy, respectively, as well as discrete seawater measurements of pCO 2 and total dissolved inorganic carbon (TCO 2 ) obtained during a number of field campaigns. A relationship between NSS alkalinity and salinity was developed with the discrete datasets and used with the continuous measurements to highly resolve the marine CO 2 system. Collectively, these datasets provided insights into the seasonality in this historically under-sampled region and detail the area’s tendency for aragonite saturation state (Ω arag ) to be at non-corrosive levels (i.e., Ω arag > 1) only in the upper water column during spring and summer months. This depth zone and time period of reprieve can be periodically interrupted by strong northwesterly winds that drive short-lived (∼1 week) episodes of high-pCO 2 , low-pH, and low-Ω arag conditions throughout the region. Interannual variability in summertime conditions was evident and linked to reduced northwesterly winds and increased stratification. Anthropogenic CO 2 in NSS surface water was estimated using data from 2017 combined with the global atmospheric CO 2 forcing for the period 1765 to 2100, and projected a mean value of 49 ± 5 μmol kg -1 for 2018. The estimated trend in anthropogenic CO 2 was further used to assess the evolution of Ω arag and pH T levels in NSS surface water, and revealed that wintertime corrosive Ω arag conditions were likely absent pre-1900. The percent of the year spent above Ω arag = 1 has dropped from ∼98% in 1900 to ∼60% by 2018. Over the coming ...